Contested history of Neo-classical economic models of households in development - Chowdhury, Jahan (BRAC University, 2010)
The models outlined in this essay were basically put together to help economists analyze household behavior and subsequently propose government policies for poverty reduction. From the arguments posed in the above text, it is clear that government policies should not be based solely on the unitary model because of its failure to analyze intra household relationships and resource distribution.